The Effect of Oxytocin Massage on Increasing Breast Milk Production in Postpartum Mothers in the Working Area of Pusian Public Health Center - Novia Denada Manopo; Sulistiyah Sulistiyah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background: Low exclusive breastfeeding coverage is often caused by mothers' concerns thatl their breast milkl production isl insufficient. Oxytocinl massage isl a lnon-pharmacologicall solution thatl can stimulatel the oxytocinl hormone tol facilitate milk llet-ldown. Objective: Thisl study aimedl to determine thel effect ofl oxytocin massagel on increasingl breast milkl production inl postpartum mothersl in thel working areal of Pusian Public Healthl Center. lMethods: Thisl quantitative research used al pre-experimentall design withl a One Group lPretest-Posttestl approach. Thel sample consistedl of 30 postpartum mothers selectedl using total lsampling. Datal analysis was performed usingl the Pairedl T-Testl statistical test. lResults: Before thel oxytocin massage, thel majority ofl respondents hadl inadequate breastl milk productionl (66.7%). Afterl receiving the oxytocinl massage intervention, thel majority ofl respondents (86.7%) experiencedl an increasel in breastl milk productionl to thel adequate category. Statisticall test resultsl showed al p-valuel of l0.000l (pl < l0.05). lConclusion: Oxytocinl massage hasl a significantl effect on increasingl breast milkl production inl postpartum mothersl in thel working areal of Pusian Public Healthl Center.